Psychosocial Development Of The Character Maik Klingenberg In The Novel “Tschick” By Wolfgang Herrndorf - Tambunan, Rut Isabella; Simanjuntak, Tarida Alvina; Hutagalung, Insenalia S.R. (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
This study aims to describe: 1) the psychosocial development of the main character, Maik Klingenberg, in Wolfgang Herrndorf's novel Tschick based on Erikson's theory, particularly the stage of identity vs. role confusion, and 2) the factors influencing Maik's identity formation, including family, social environment, and school. The research employed a descriptive qualitative method with a literary psychology approach. The primary data source was the original German edition of Tschick (2010). Data were collected using the reading-and-note-taking technique and analyzed through classification according to Erikson's psychosocial indicators. The findings reveal that Maik experiences an identity crisis characterized by social role confusion, feelings of alienation, and emotional instability. Through his journey with Tschick, Maik undergoes a process of identity exploration that includes trying new roles, developing independence, and engaging in self-reflection. Eventually, Maik reaches a more mature stage of identity formation. This research contributes to the interdisciplinary study of literature and psychology, and provides practical implications for character education, especially